COMT gene polymorphism in a sample of pregnant women with intruterine growth restriction in a Lima hospital - Pacheco-Romero, José (2013)
Background: Cellular and molecular events in the pathophysiology of intrauterine growth restriction (IUGR) are still unknown. Cathecol-O-methyltransferase (COMT) is a phase II enzyme that inactivates cathecol estrogens by transferring a methyl group. A functional polymorphism Val158 Met in COMT gene is known as susceptible marker for diverse maternal and perinatal diseases, and studies suggest the allele codifying a low activity COMT may be a susceptible marker for IUGR. COMT polymorphism study may be a new strategy to determine genetic markers that might be used for detection of certain disorders related to pregnancy. Objectives: To determine association of Val158Met cathecol-O-methyltransferase (COMT) polymorphism and intrauterine growth restriction. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Design: Relational (associative), observational, casecontrol (non-experimental) study. Materials: Maternal blood samples obtained following delivery. Methods: During 2011, 81 blood samples were obtained from post partum mothers for COMT gene genotyping, 26 (32.1%) were mothers with IUGR (cases) and 55 (67.9%) without IUGR (controls). Genotype distribution was determined by chi square test. Genotypes proportional distribution in IUGR and non-IUGR groups was determined with Hardy-Weinberg’s null hypothesis. All women signed informed consent. Main outcome measures: Association of COMT genotypes and IUGR, and between COMT Val/Met alleles and IUGR. Results: Genotype distribution in IUGR and non-IUGR groups agreed with Hardy-Weinberg null hypothesis. There was no association of COMT Val/Met genotypes and IUGR, X2=1.8057, gl=2, p=0.4054. There was no association between COMT Val/Met alleles and IUGR, X2=0.3659, gl=1, p=0.5453. Conclusions: No association was found either between COMT genotypes and IUGR or between COMT Val/Met alleles and IUGR.